Coastal Water Quality in an Atlantic Sea Bass Farm Site (Sines, Portugal): A First Assessment - Gomes, Mara; Correia, Alexandre; Pinto, Lígia; Sá, Carolina; Brotas, Vanda; Mateus, Marcos (Frontiers in Marine Science, 2020)
Aquaculture has become the fastest growing sector of the food industry worldwide. However, the increase of intensive aquaculture practices has been raising global concern about economic and social impacts, but mostly due to the associated potential environmental impacts. The aim of this report is to make a preliminary assessment on the impact of a seabass aquaculture (Dicentrarchus labrax) on the surrounding coastal waters. The aquaculture site is located at the SW Iberian coast (Sines, Portugal), having 16 cages, each holding around 150 000 specimens at different stages of growth. We present a spatial and temporal description of environmental physical, chemical and biological parameters taken in the course of four monitoring campaigns (June 2018 to April 2019). All monitored parameters showed values within the natural range of coastal waters. So far, results don’t reveal any detrimental impact of the production units on local water quality, although more research is needed. The preliminary findings point to the hydrodynamic regime in the production area, and to the feeding strategy and the dimension of production units as the reasons for the lack of stress on the receiving waters.